2018
DOI: 10.1002/pssb.201800489
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cracks on Anomalous Mechanical Behavior and Energy Dissipation of Negative‐Stiffness Plates

Abstract: Mechanical behavior of negative-stiffness (NS) plates containing cracks, under sinusoidal straining, are numerically studied with the phase-field modeling techniques. Ferroelastic phase transition is triggered by thermal loading with the Landau-type energy function to generate the double-well potential. NS arises from regions of the multi-domain plates, and interacts with surrounding positive-stiffness neighboring regions to give rise to anomalous mechanical behavior and energy dissipation. It is found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Novel fabrics with auxetic properties [28,29,30,31], targeted for personal applications have been developed. Alongside the experimental studies, new theoretical models exhibiting negative Poisson's ratio [32,33,34,35,36,37,38,39,40,41,42,43,44,45,46] have been proposed. The search for the negative Poisson's ratio in known and naturally occurring materials revealed that around 70% of metals with cubic symmetry have such properties [47].…”
Section: Introductionmentioning
confidence: 99%
“…Novel fabrics with auxetic properties [28,29,30,31], targeted for personal applications have been developed. Alongside the experimental studies, new theoretical models exhibiting negative Poisson's ratio [32,33,34,35,36,37,38,39,40,41,42,43,44,45,46] have been proposed. The search for the negative Poisson's ratio in known and naturally occurring materials revealed that around 70% of metals with cubic symmetry have such properties [47].…”
Section: Introductionmentioning
confidence: 99%
“…[19,20] In this work, we use the more recent classification [20] which distinguishes between nonauxetics, partial auxetics, and auxetics. Vast potential applications of auxetic materials drive the theoretical and experimental investigations, which branch into auxetic metamaterials, [21][22][23][24][25][26][27][28] models, [16,[29][30][31][32][33][34][35][36][37][38][39][40][41] structures, [42][43][44][45][46][47][48] polymers, [49,50] composites, [51] foams, [52][53][54] and fabrics. [55][56][57][58] Most of the research on auxetics is focused either on developing new materials or searching for auxetic properties in existing ones.…”
Section: Introductionmentioning
confidence: 99%
“…[20] Using the phase field modeling, NS effects have been examined without directly assigning negative modulus values in calculations. [21,22] In addition, NS effects on the overall viscoelastic and coupled field properties have been investigated with the finite element analysis. [23] Furthermore, energy dissipation of a viscoelastic composite beam-column connector has been numerically analyzed to exhibit its high stiffness and high damping.…”
Section: Introductionmentioning
confidence: 99%
“…The inter‐relations between negative compressibility and NPR have been demonstrated that they are attainable . Using the phase field modeling, NS effects have been examined without directly assigning negative modulus values in calculations . In addition, NS effects on the overall viscoelastic and coupled field properties have been investigated with the finite element analysis .…”
Section: Introductionmentioning
confidence: 99%